Faktor yang mempengaruhi intensi mengonsumsi kopi organik di kalangan anak muda - Chairy, Chairy (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2017)
Recently coffee of Indonesia become major attention of world coffee importers as Indonesia has variety of specialty coffee. Drinking coffee is believed as one of trending activities of young people in urban area. This study examined factors affecting intention to consume organic coffee.Ã‚Â The sample was 200 undergraduate students of Universitas Tarumanagara who are coffee drinkers. The dependent of this research is intention to consume. Independent variables consist of four variables, they are spirituality, environmental concern, helath concern, and lifestyle. By using regression analysis, this study revealed that spirituality and lifestyle affect intention to consume organic coffee significantly. On the other hand, contrary to previous research, the effect of environmental concern and health concern on intention to consume organic coffee was not significant. This research finding may help marketers of organic coffee in designing their marketing program. They may pay more attention to spirituality and lifestyle aspects in order to suceed in gaining more market share.